REVIEW OF ISLAMIC CRIMINAL LAW AGAINST CRIMINAL ACTION OF ABUSE OF SHARP WEAPONS - AZ, Mutiara (JCH (Jurnal Cendekia Hukum), 2023)
Carrying a sharp weapon is a criminal act which can cause harm to other people, both on property and even killing other people. In addition to the consequences, carrying a sharp weapon can also cause harm to the criminal himself. The sharp weapon misuse is actually not a new thing. It is a form of crime as stipulated in Article 2 Paragraph 1 of the Emergency Decree Number 12 year 1951. The objectives of this study were to find out how was the basis for judges' considerations in imposing criminal sanctions and the review of  Islamic criminal law in adjudication  of District Court of Palembang Number 821/Pid.Sus/2020/PN.Plg. The method used was the Normative legal research method, which was obtained from literature review (Library Research). The results of the study showed that before imposing a criminal decree, the judge first payed attention and considered the basic principles of justice, legal certainty, utility in imposing a sentence based on the crime committed by the defendant.